Lactone Component From Ligusticum chuanxiong Alleviates Myocardial Ischemia Injury Through Inhibiting Autophagy - Wang, Gang; Dai, Guoliang; Song, Jie; Zhu, Maomao; Liu, Ying; Hou, Xuefeng; Ke, Zhongcheng; Zhou, Yuanli; Qiu, Huihui; Wang, Fujing; Jiang, Nan; Jia, Xiaobin; et al. (Frontiers in Pharmacology, 2018)
The dysregulation of autophagy is associated with a series of cardiovascular diseases, such as myocardial ischemia injury. Lactone component from Ligusticum chuanxiong (LLC) is the major constituent of the traditional Chinese herb Ligusticum chuanxiong Hort., which has been reported to hold potential cardioprotective effects. In this study, to determine whether LLC protects the heart through regulation of autophagy, we explored the effects of LLC on cardioprotection and autophagy in myocardial ischemia injured rats and H9c2 cardiomyocytes. Our results showed that LLC significantly reduced infarct size and serum levels of lactate dehydrogenase, creatine kinase, and cardiac troponin and ameliorated histological features in a dose-dependent manner. Similar protections were observed in cardiomyocytes subjected to oxygen-glucose deprivation (OGD). Meanwhile, LLC inhibited autophagy induced by myocardial ischemia injury, characterized by increased autophagic vacuoles, LC3-Ⅱ/LC3-Ⅰ ratio and the expression of Beclin 1, whereas decreased the expression of p62. Additionally, LLC combined with a lysosomal inhibitor chloroquine (CQ) reduced LC3-Ⅱ/LC3-Ⅰ ratio in cardiomyocytes compared with CQ alone. Furthermore, LLC-afforded cardioprotection was abolished by a specific PI3K inhibitor LY294002. Collectively, these findings demonstrated that cardioprotective effects of LLC were related to restoration of autophagic flux through the activation of PI3K/Akt/mTOR signaling pathway.